2009
DOI: 10.1073/pnas.0903944106
|View full text |Cite
|
Sign up to set email alerts
|

MIWI-independent small RNAs (MSY-RNAs) bind to the RNA-binding protein, MSY2, in male germ cells

Abstract: The germ cell-specific DNA/RNA-binding protein MSY2 binds small RNAs (MSY-RNAs) that are Ϸ25-31 nt in length, often initiate with a 5 adenine, and are expressed in both germ cells and somatic cells. MSY-RNA levels do not decrease in Miwi or Msy2 null mice. Most MSY-RNAs map within annotated genes, but some are PIWIinteracting RNA (piRNA)-like and map to piRNA clusters. MSY-RNAs are in both nuclei and cytoplasm. In nuclei, MSY-RNAs are enriched in chromatin, and in the cytoplasm they are detected in both ribonu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2009
2009
2014
2014

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(10 citation statements)
references
References 30 publications
0
9
0
Order By: Relevance
“…Rabbit anti-Miwi antibody raised against the peptide VIRVPAPCQYAHKLAFLVGQ (amino acids 826–845) and mouse anti-actin antibody (Sigma) were used for immunoblotting as described in (42). …”
Section: Methodsmentioning
confidence: 99%
“…Rabbit anti-Miwi antibody raised against the peptide VIRVPAPCQYAHKLAFLVGQ (amino acids 826–845) and mouse anti-actin antibody (Sigma) were used for immunoblotting as described in (42). …”
Section: Methodsmentioning
confidence: 99%
“…Although the properties of MSY2 as an mRNA binding protein have previously been studied, recent work suggested that it might also bind small RNAs. Therefore a "directed-CLIP" experiment was done in which small RNA-protein complexes were isolated on the basis of elecrophoretic mobility 91 . 231 CLIP tags were sequenced and found to be small RNAs expressed in testes ranging in length from 18 to 36 nt.…”
Section: Clip To Pirna and Other Small Rnas; Msy2 Clip-msy2mentioning
confidence: 99%
“…MSY2, a germ-cell-specific member of the Y-box family of DNA-/RNA-binding proteins, have recently been shown to associate with a novel class of small RNAs. MSY2 binds small RNAs (MSY-RNAs) that range in size from 18–36 nt with the majority being 25–31 nt in length, and are expressed in both germ cells and somatic cells [54]. Despite the abundance of piRNAs in the testes which are also similar in size to the immunoprecipitated RNAs with MSY; the authors found only 7% of these MSY-RNA map to known piRNA genes.…”
Section: Small Rnas Based Ribonucleic-protein Interactionsmentioning
confidence: 99%